Bio-based aromatic copolyesters : influence of chemical microstructures on thermal and crystalline properties - Hu, Keling (2021)
Aromatic copolyesters, derived from bio-based nipagin and eugenol, were synthesized with renewable 1,6-hexandiol as the spacer. Number-average, weight-average molecular weights (Mn, Mw), and polydispersity (D) values were determined by size exclusion chromatography (SEC). Chemical structures were confirmed by 1H NMR and 13C NMR spectroscopies. Chemical microstructure analysis suggested that the nipagin and eugenol-derived units were inserted into polymer chains in an arbitrary manner. Due to the short chain of 1,6-hexanediol, the splitting of magnetically different methylene carbons, adjacent to the alcohol-oxygens, proved to be more sensitive towards sequence distributions, at the dyed level, than those from 1,10-decanediol. Thermal gravimetric analysis (TGA) demonstrated that these polyester materials have excellent thermal stability (>360 °C), regardless of the content of eugenol-derived composition incorporated. Differential scanning calorimetric (DSC) and wide-angle X-ray diffraction (WXRD) experiments revealed the semicrystalline nature for this kind of copolyesters. The crystallinities gradually decreased with the increase of eugenol-derived composition. Thermal and crystalline properties were well discussed from the microscopic perspective. The point of this work lies in establishing guidance for future design and modification of high-performance polymer materials from the microscopic perspective.